The day-of-week (DOW) effect on liberalism-conservatism: Evidence from a large-scale online survey in China - Ye, Shengquan; So, Justin Juk Man; Ng, Ting Kin; Ma, Mac Zewei (Frontiers in Psychology, 2023)
Past research has shown that psychological states tend to fluctuate across the days of a week, which is referred to as the day-of-week (DOW) effect. Based on a large-scale online survey (n = 171,830), this study investigated the DOW effect on liberalism-conservatism among Chinese people by testing two competing hypotheses. According to the cognitive states hypothesis, it was predicted that liberalism would be high on Mondays but gradually decrease to Fridays due to the depletion of cognitive resources over the weekdays. In contrast, the affective states hypothesis predicted the opposite, considering the more positive affect brought by the approaching weekends. Both hypotheses predicted the level of liberalism would peak at weekends. Results showed the level of liberalism decreased gradually from Mondays until Wednesday, rebounded from Wednesdays to Fridays, and peaked at weekends. The V-shaped pattern suggested that the DOW fluctuation in liberalism-conservatism could derive from the synergy of both cognitive and affective processes, instead of either one alone. The findings have important implications for practice and policy-making, including the recent pilot scheme of 4-day workweek.